The Distribution of Economic and Educational Capital between School Catchment Areas in Reykjavík Capital Region 1997–2016 - Magnúsdóttir, Berglind Rós; Auðardóttir, Auður Magndís; Stefánsson, Kolbeinn (Stjórnsýslustofnun, 2020)
It is well established that parental income, wealth, and education substantially affects school districts. In this article, we examine differences between school districts in the capital region of Iceland among parents having children in compulsory schools. The article is based on tailored statistics provided by Statistics Iceland covering the period from 1997–2016. We focus on distributions of parents that have Icelandic origin and have the highest levels of education, income, and wealth. This group of parents has access to neighbourhood choice and the symbolic capital to shape the grapevine on schools and neighbourhood qualities. Even though educational qualification and wealth grew during the period under study, the gains have been geographically uneven throughout the capital city region. Five of 42 school districts stand out in terms of economic and educational capitals. Three stand out in terms of income and wealth and two in terms of high levels of educational capital that are most valued by the cultural elite. These geographical boundaries visibly divide the upper class into two fractions depending on which kind of capital is dominant. Three neighbourhoods stand out in terms of low levels on capital on all dimensions. Samsetning foreldrahópa með tilliti til efnahags, uppruna og menntunar hefur afgerandi áhrif á hvert skólasamfélag. Í þessari rannsókn er stéttaaðgreining milli skólahverfa skoðuð með fræðilegum hætti í íslensku borgarsamfélagi. Byggt er á auðshugtökum Bourdieu við öflun og greiningu á sérvinnslugögnum um foreldra grunnskólabarna frá Hagstofu Íslands 1997–2016. Farin var sú leið að skoða sérstaklega dreifingu foreldra sem hafa mestan efnahags- og menntunarauð og hafa fjölskyldutengsl til Íslands, því þau eru líklegust til að hafa raunverulegt val og táknrænan auð til að móta hugmyndir um gæði skóla og hverfa. Hér er dregin fram landfræðileg aðgreining milli efnahagsauðs- og menningarauðsstéttar í íslensku borgarsamfélagi. Erlendur uppruni, menntunar- og efnahagsauður hafa almennt vaxið ...